CHEMICAL AND BIOLOGICAL PROFILING OF GRAPE SHOOT PHENOLICS: ANTIOXIDANT, ANTIMICROBIAL, AND ENZYME INHIBITORY ACTIVITIES - Fatima Kamah; Abdelkader Basli; Amina Merzoug; Amina Bouzana; Amina Bougouizi; Ramazan Erenler; Ilyas Yildiz; Chawki Bensouici; Fouzi Boulkenafet; Simonetta Lambiase; Mohammed A. Wadaan; Fahd A. Al-Meklafi (Journal of Animal and Plant Sciences, 2025)
Fruits and vegetables are rich in polyphenols, which are secondary metabolites that are essential for both human health and plant defense.This study investigates whether grape shoot debris from two different grape varieties Vitis vinifera and Vitis labrusca—can provide polyphenols.It also looks at how well they combat bacteria, oxidation, and certain enzymes.Grape shoots from Boumerdes and Baghlia were gathered, and 60% ethanol was used to extract them.Thirteen phenolic compounds were discovered by LC-MS/MS, with flavanols being the most prevalent.The primary substance present in all extracts was Catechin.The Fregola Nera variety has the largest quantity at (1449.45 mg/kg DW), followed by the Cardinal variety at (753.53 mg/kg DW).As assessed by phenanthroline tests using silver nanoparticles, the antioxidant activity demonstrated a concentration-dependent impact.The highest antioxidant potential was demonstrated by the Fregola Nera and Cardinal types, which had A0.5 values of 45.12 µg/mL and 49.87 µg/mL, respectively.Strong anti-tyrosinase action was demonstrated by the extracts.The inhibition rate of the Fregola Nera extract was 46.44%, comparable to that found in standard kojic acid (49.46%).With an IC50 value of 25.88 µg/mL, the Cardinal variant demonstrated potent anti-urease activity, blocking 80% at a dosage of 200 µg/mL.This is comparable to the reference inhibitor thiourea, which has an IC50 of 11.57 µg/mL and 98.90% inhibition.Salicylic acid, o-coumaric acid, and gallic acid were the most attracted to urease, according to molecular docking studies. Their binding strengths were -28.88 kJ/mol, -26.51 kJ/mol, and -24.69 kJ/mol, respectively.When the extracts' antibacterial activity was evaluated against Candida albicans and Escherichia coli, it showed significant inhibition. The largest inhibition zone against E. Coli (15 mm) and Candida albicans (20 mm) was seen in the Fregola Nera extract, whereas the Cardinal extract demonstrated inhibition against E. Coli of 16 mm and Candida albicans of 15 mm.All extracts had a minimum inhibitory concentration (MIC) of 6 mg/mL.These findings demonstrate that grape shoot waste can be a valuable source of polyphenols, which have potent antibacterial, antioxidant, and enzyme-blocking properties.This encourages its application in environmentally friendly waste management and health-related products.
Keywords: grape; shoot; polyphenols; flavonoids; antioxidant; urease.